Optimizing Steam Consumption of Mushroom Canning Process by Selecting Higher Temperatures and Shorter Time of Retorting - Didik J. Pursito; Eko H. Purnomo; Dedi Fardiaz; Purwiyatno Hariyadi (International Journal of Food Science)
Increasing energy cost has driven the food canning industries to optimize their energy consumption in order to produce safe and shelf-stable foods efficiently. In the mushroom canning industry, energy efficiency is very critical to improve product (price) competitiveness. This research aimed at demonstrating total steam consumption to achieve the same sterility level (F0-value) of canned mushroom by using different combinations of times and temperatures of retorting. Agaricus bisporus in brine contained in 300×407 cans was heat processed in a horizontal static retort. Three different retort temperatures (115, 121, and 130°C) and different operator processing times ranging from 2 to 97 minutes were employed to achieve different levels of F0-values. Our results showed that at the same level of sterility, steam consumption inversely decreased with the increase of retort temperature. At the same F0-value of 10 minutes, energy efficiency for up to 72.9% and 58.1% per batch of retorting was achieved by increasing the temperature from 115 to 130°C and 115 to 121°C, respectively. Since steam consumption is a major element of production costs in the canning industry, the selection of higher temperatures and shorter time of retorting will have a positive commercial impact due to the reduction of production costs.